Higher Education in Nepal (Pravaha, 2018)
Background - Higher education is very important for the development of the nation. It is recognized today as a capital investment and is of paramount importance for economic andsocial development of the country. Quality higher education is a source of great potential for the socio economic and cultural development of the country. The nation can be transformed into a developed nation within the life time of a single generation.Purpose – The purpose of the study is to study about the effectiveness of higher education of Nepal.Methodology – Due to the specific nature of the research objectives, descriptive cum analytical research design has been used.Findings – Higher Education in Nepal is satisfactory and every stakeholders of the Nepal have been satisfied with the performance of the higher education of Nepal.Practical Implications - This study has widely tested the effectiveness of the higher education in Nepal. It helps to improve the quality of higher education in Nepal.Pravaha Vol. 24, No. 1, 2018, page: 96-108